Correlations between quantitative T2 and T1ρ MRI, mechanical properties and biochemical composition in a rabbit lumbar intervertebral disc degeneration model. Issue 8 (10th August 2016) - Gullbrand, Sarah E.; Ashinsky, Beth G.; Martin, John T.; Pickup, Stephen; Smith, Lachlan J.; Mauck, Robert L.; Smith, Harvey E.
ABSTRACT: Improved diagnostic measures for intervertebral disc degeneration are necessary to facilitate early detection and treatment. The aim of this study was to correlate changes in mechanical and biochemical properties with the quantitative MRI parameters T 2 and T 1 ρ in rabbit lumbar discs using an ex vivo chymopapain digestion model. Rabbit lumbar spinal motion segments from animals less than 6 months of age were injected with 100 μl of saline (control) or chymopapain at 3, 15, or 100 U/ml ( n  = 5 per group). T 2 and T 1 ρ MRI series were obtained at 4.7T. Specimens were mechanically tested in tension–compression and creep. Normalized nucleus pulposus (NP) water and GAG contents were quantified. Stepwise multiple linear regression was performed to determine which parameters contributed significantly to changes in NP T 2 and T 1 ρ . When all groups were included, multiple regression yielded a model with GAG, compressive modulus, and the creep time constants as variables significantly impacting T 2 (multiple r 2  = 0.64, p  = 0.006). GAG and neutral zone (NZ) modulus were identified as variables contributing to T 1 ρ (multiple r 2  = 0.28, p  = 0.08). When specimens with advanced degeneration were excluded from the multiple regression analysis, T 2 was significantly predicted by compressive modulus, τ 1, and water content (multiple r 2  = 0.71, p  = 0.009), while no variables were significant predictors in the model for T 1 ρ . These results indicate that quantitative MRI can detect changes in the mechanical and biochemical properties of the degenerated disc. T 2 may be more sensitive to early stage degenerative changes than T 1 ρ, while both quantitative MRI parameters are sensitive to advanced degeneration. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1382–1388, 2016.